Energy spectrum of a hierarchical superlattice with impurities in potential barriers - Korol, Anatoliy (My University, 1994)
A 1D superlattice in which a hierarchical modulation of the potential is caused by impurity centers in potential barriers is discussed. A transfer-matrix method is used to calculate and analyze the tunneling spectra of this hierarchical superlattice.
Keywords: impurities; hierarchical superlattice; energy spectrum; домішки; ієрархічні надгратки; енергетичний спектр; энергетический спектр; примеси; иерархические сверхрешетки; кафедра фізики та професійної безпеки